La traduction à quatre roues - Larose, Robert (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractTranslation has been associated to traitors, mirors, unfaithful women... and, more recently, to a large-scale means of mass transportation: the automobile. But is translation a four-wheel drive? How does one go about approching his/her object of inquiry, whether it be an automobile or translation? What are the access roads, the bumps and dead ends? Shouldn't researchers take a driver's seat approach to the open road? Finally, is translation merely a vehicule for traveling between places, or can it also be a metonymical figure for something else?